Factors influencing the use of derivatives in Poland - Mizerka, Jacek; Stróżyńska-Szajek, Agnieszka (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
Taking into account the ambiguous results of research concerning the impact of the use of derivatives on a firm’s value, we propose a more complex approach that would better explain the role of derivatives. We investigate the factors influencing derivatives usage by 308 nonfinancial firms listed on the Warsaw Stock Exchange for the period of 2008-2011. We also test the hypothesis saying that there are differences in the factors influencing the use of derivatives by companies in developed economies and by companies operating in transition economies. To examine the direction of the influence of certain factors on derivatives usage and the significance of that influence, we use a logit model. To explore the impact of a specific group of factors, we construct 47 different logit models using a combination of variables reflecting firm’s size, default risk, debt service costs, liquidity constraints, and growth options. Owing to specific time-series cross-sectional data, we used a method of building a model based on panel data. The results of our analysis indicate that such factors as company size, risk of default and debt usage have a significant positive effect on derivatives usage. According to our results there is no permanent, statistically significant relationship between derivative usage by Polish companies and liquidity ratios. In all models, considering an option to develop, this factor has a significant negative impact on derivative usage. In general, we have obtained results showing the similarity of the factors that affect the use of derivatives by companies operating in Polish and foreign markets
Argumenta Oeconomica, 2018, Nr 1 (40), s. 5-20
Keywords: derivatives; risk management; hedging